Bumble Bees (Hymenoptera: Apidae) Respond to Moth (Lepidoptera: Noctuidae) Pheromone Components, Leading to Bee Bycatch in Monitoring Traps Targeting Moth Pests - Grocock, Nicholas L.; Batallas, Ronald E.; McNamara, Emily A.; Sturm, Ashton B.; Manson, Jessamyn S.; Evenden, Maya L. (Frontiers in Ecology and Evolution, 2020)
Semiochemical-baited traps are commonly used to monitor moth pests and inform management decisions. Unfortunately, bee pollinators can be unintentionally captured, which reduces monitoring system efficiency and may negatively impact pollinator biodiversity and pollination services. We assessed the abundance and diversity of wild bees captured in semiochemical-baited traps designed to capture cutworm and armyworm (Lepidoptera: Noctuidae) pests in North America. Green Unitraps were baited with semiochemicals including: 1) species-specific noctuid pheromone lures; 2) food bait lures consisting of fermentation by-products; or 3) floral volatiles. Traps were positioned in canola (Brassica napus L.) and wheat (Triticum aestivum L.) fields in Alberta, Canada. We also explored the mechanisms of bee detection of moth pheromone components using electroantennogram (EAG) assays to assess the antennal response of two Bombus species. We found that more bumble bees (Hymenoptera: Apidae), and especially Bombus rufocinctus Cresson, were captured in traps baited with moth pheromone lures than in unbaited control traps. Fermentation by-product lures captured a similar low number of bees as unbaited traps, whereas floral volatile-based food bait lures captured more bees, comparable to capture in pheromone-baited traps. In general, more Bombus spp. were captured in traps positioned at canola vs. wheat fields, but the community composition was similar among crops. EAG assays indicate that sensory receptors on the antennae of B. rufocinctus Cresson and B. impatiens Cresson detect noctuid moth pheromones. Perception of chemical signals of a different insect order may be explained by structural similarities in pheromone components produced by both moths and bumble bees.